Environmental tax reform and the double dividend: An econometric demand analysis - Christian M. Scholz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper examines the empirical relevance of the double dividend of revenue neutral marginal environmental tax reforms. For this purpose we use an extended version of the Ahmad-Stern model of indirect taxation. This version includes environmental externalities. We estimate the key parameters of the model with different dynamic specifications of the Almost Ideal Demand System. We find no evidence that a revenue neutral environmental tax reform that increases the energy or gasoline tax yields a double dividend.
Keywords: D12; H21; H23; H31; Q41; 330; Umweltabgabe; Steuerreform; Deutschland